Mechanical properties of sandstone under in-situ high-temperature and confinement conditions - Liu, Liyuan; Jin, Juan; Liu, Jiandong; Cheng, Wei; Zhao, Minghui; Luo, Shengwen; Luo, Yifan; Wang, Tao (International journal of minerals, metallurgy and materials, 2025)
Low- to medium-maturity oil shale resources display substantial reserves, offering promising prospects for in-situ conversion in China. Investigating the evolution of the mechanical properties of the reservoir and caprock under in-situ high-temperature and confinement conditions is of considerable importance. Compared to conventional mechanical experiments on rock samples after high-temperature treatment, in-situ high-temperature experiments can more accurately characterize the behavior of rocks in practical engineering, thereby providing a more realistic reflection of their mechanical properties. In this study, an in-situ high-temperature triaxial compression testing machine is developed to conduct in-situ compression tests on sandstone at different temperatures (25, 200, 400, 500, and 650°C) and confining pressures (0, 10, and 20 MPa). Based on the experimental results, the temperature-dependent changes in compressive strength, peak strain, elastic modulus, Poisson’s ratio, cohesion, and internal friction angle are thoroughly analyzed and discussed. Results indicate that the mass of sandstone gradually decreases as the temperature increases. The thermal conductivity and thermal diffusivity of sandstone exhibit a linear relationship with temperature. Peak stress decreases as the temperature rises, while it increases with higher confining pressures. Notably, the influence of confining pressure on peak stress diminishes at higher temperatures. Additionally, as the temperature rises, the Poisson’s ratio of sandstone decreases. The internal friction angle also decreases with increasing temperature, with 400°C acting as the threshold temperature. Interestingly, under uniaxial conditions, the damage stress of sandstone is less affected by temperature. However, when the confining pressure is 10 or 20 MPa, the damage stress decreases as the temperature increases. This study enhances our understanding of the influence of in-situ high-temperature and confinement conditions on the mechanical properties of sandstone strata. The study also provides valuable references and experimental data that support the development of low- to medium-maturity oil shale resources.